Insight into the soil bacterial community succession of Nicotiana benthamiana in response to Tobacco mosaic virus - Zhao, Yuqiang; Liu, Tianbo; Wu, Shaolong; Zhang, Deyong; Xiao, Zhipeng; Ren, Zuohua; Li, Lingling; Liu, Suoni; Xiao, Yunhua; Tang, Qianjun (Frontiers in Microbiology, 2024)
Background: Tobacco mosaic virus (TMV) is one famous plant virus responsible for substantial economic losses worldwide. However, the roles of bacterial communities in response to TMV in the tobacco rhizosphere remain unclear.We explored the soil physicochemical properties and bacterial community succession of the healthy (YTH) and diseased (YTD) plants with TMV infection by 16S rRNA gene sequencing and bioinformatics analysis.We found that soil pH in the YTD group was significantly lower than in the YTH group, and the soil available nutrients were substantially higher. The bacterial community analysis found that the diversity and structure significantly differed post-TMV disease onset. With TMV inoculated, the alpha diversity of the bacterial community in the YTD was markedly higher than that in the YTH group at the early stage. However, the alpha diversity in the YTD group subsequently decreased to lower than in the YTH group. The early bacterial structure of healthy plants exhibited higher susceptibility to TMV infection, whereas, in the subsequent stages, there was an enrichment of beneficial bacterial (e.g., Ramlibacter, Sphingomonas, Streptomyces, and Niastella) and enhanced energy metabolism and nucleotide metabolism in bacteria.The initial soil bacterial community exhibited susceptibility to TMV infection, which might contribute to strengthening resistance of Tobacco to TMV.